Familiarity or conventionality? Investigating relevant factors in metaphor processing - Silva, Gladiston Alves da (2021)
Are metaphors processed by the listener more slowly than literal expressions? To what extent can the speaker's familiarity with metaphorical expressions accelerate the process of understanding them? Studies on metaphor processing show divergences as to how this figure of speech is interpreted. Some authors argue that metaphors are processed more slowly than literal expressions, given the need to observe the three stages for understanding provided for in the Standard Pragmatic Model (SEARLE, 1979). Evidence of the indirect processing of metaphors, compatible with the aforementioned model, is reported in the literature (JANUS and BEVER, 1985). The priority of literal over metaphorical meaning has, however, been questioned by other studies that defend the direct processing of metaphorical expressions (GLUCKSBERG, 2003; RICCI, 2016). A third theoretical wave aims to reconcile the hitherto conflicting theories, proposing that, depending on the degree of conventionality of the metaphorical vehicle, a metaphor can be processed more slowly or at the same time as literal expressions (BOWDLE and GENTNER, 2005). In this framework, our study rescues the importance of familiarity already indicated as a relevant factor in a previous experimental study (SILVA, 2018). Here, we present new evidence, based on a psycholinguistic self-paced reading experiment, that the effective control of the metaphor's cognitive processing rests on the familiarity of the expression and not on the conventionality of the vehicle, as has been pointed out by most theorists.